2003
DOI: 10.1152/ajpcell.00322.2002
|View full text |Cite
|
Sign up to set email alerts
|

Activation of gene expression in human neutrophils by high mobility group box 1 protein

Abstract: High mobility group box 1 (HMGB1) protein, a DNA binding protein that stabilizes nucleosomes and facilitates transcription, was recently identified as a late mediator of endotoxin lethality. High serum HMGB1 levels in patients with sepsis are associated with increased mortality, and administration of HMGB1 produces acute inflammation in animal models of lung injury and endotoxemia. Neutrophils occupy a critical role in mediating the development of endotoxemia-associated acute lung injury, but previously it was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
267
2
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 390 publications
(284 citation statements)
references
References 50 publications
(88 reference statements)
14
267
2
1
Order By: Relevance
“…HMGB1 can induce the secretion of TNF-a and IL-1b from human monocytes and neutrophils. 31,32 However, we did not detect a any direct effect of HMGB1 on the secretion of TGF-b1 from a variety of related cell lines. Other cells that are potential sources of TGF-b1, such as vascular smooth muscle cells, were not assessed.…”
Section: Discussioncontrasting
confidence: 66%
“…HMGB1 can induce the secretion of TNF-a and IL-1b from human monocytes and neutrophils. 31,32 However, we did not detect a any direct effect of HMGB1 on the secretion of TGF-b1 from a variety of related cell lines. Other cells that are potential sources of TGF-b1, such as vascular smooth muscle cells, were not assessed.…”
Section: Discussioncontrasting
confidence: 66%
“…We and others have shown that ERK activity increases as early as 0.5 to 1 h after ischemia in the middle cerebral artery territory (Alessandrini et al, 1999;Wu et al, 2000). This signaling is potentially linked to TLR2, TLR4, and/or RAGE activation (Ishihara et al, 2003;Park et al, 2003;Taguchi et al, 2000) and is known to promote transcription of cytokines such as TNFa (Fiuza et al, 2003). Tumor necrosis factor a mRNA reportedly increases within 1 h after induction of ischemia in the periinfarct and infarct area, peaks at 12 h, and remains elevated for up to 24 h (Gregersen et al, 2000;Lambertsen et al, 2002Lambertsen et al, , 2005Schroeter et al, 2003;Yang et al, 1999).…”
Section: Discussionmentioning
confidence: 87%
“…Highmobility group box 1 participates in nucleosome formation and regulation of gene transcription (Park et al, 2003;Stros et al, 2002). High-mobility group box 1 has recently been characterized as a key cytokine Yang et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Extracellular HMGB1 has been shown to cause multiple organ failure and contribute to the pathogenesis of divers disorders including sepsis and acute lung injury [125]. HMGB1 amplifies and extends the inflammatory response by inducing the release of other proinflammatory cytokines from many cell types, including activated macrophages and neutrophil [126]. Elevated levels of HMGB1 are present in the plasma and lung epithelial lining fluids of patients with acute lung injury and in mice exhibiting lung injury-induced by LPS instillation [127].…”
Section: Proinflammatory Responses In Hyperoxic Lung Injurymentioning
confidence: 99%
“…In addition, exposure of respiratory epithelial cells to 95% O 2 synergistically increased TNF-α-mediated activation of NF-κB and NF-κB dependent gene expression by a mechanism involving increased activation of IKK [81]. Furthermore, NF-κB plays a critical role in the release of HMGB1 into the extracellular matrix, thereby increasing the proinflammatory activity directly and evoking the production of other proinflammatory cytokines [126]. The precise mechanisms that modulate NF-κB-mediated release of HMGB1 remain unclear because neither the production nor the secretion of HMGB1 is regulated at the transcriptional level [133].…”
Section: Transcription Factors and Proinflammatory Cytokines In Hypermentioning
confidence: 99%